SALIVA SEBAGAI UJI SARING OSTEOPOROSIS - Niniarty Z. Djamal (Faculty of Dentistry, Universitas Indonesia, 2015)
Osteoporosis is a metabolic bone disease, and is characterized by low bone mass and microstructure deterioration of the bone, which leads to increased risk of fracture. Biomarker of bone metabolism can be seen as beginning of bone loss and first detection before imbalanced bone turnover comes. Biomarker of bone formation as serum bone alkaline fosfatase, osteocalcin (OC), procollagen type I, and biomarker of bone resorption as urine pyridinoline (Pyd) and deoxypyridinoline (Dpd) crosslinks, hydroxyprolin. The simultaneous examination of serum OC and urine Pyd or Dpd as a very good screening test for determination of bone imbalanced at the moment of the menopausal or the beginning of the pasca menopausal. Saliva as a potential diagnostic fluid for the assessment of osteoporosis biomarker concentrations. The study found elevated three classic warning signs for osteopororsis os OC, Dpd and 116 in the saliva of sheep without ovaries, which were similar to the levels of signs found in their blood and urine. Expectations, that the test may become available within five years and one day the test may be able to be performed at home like pregnancy test. Osteoporosis biomarker in saliva suggested detected of bone mass density easier. Beside that can be used as a method of early diagnostic and as a monitor therapy that as salinity of the examinations of bone mass on radiology.